2019
DOI: 10.1128/aem.02597-18
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of 16-Demethylrifamycins by Removing the Predominant Polyketide Biosynthesis Pathway in Micromonospora sp. Strain TP-A0468

Abstract: A number of strategies have been developed to mine novel natural products based on biosynthetic gene clusters and there have been dozens of successful cases facilitated by the development of genomic sequencing. During our study on biosynthesis of the antitumor polyketide kosinostatin (KST), we found that the genome of Micromonospora sp. strain TP-A0468, the producer of KST, contains other potential polyketide gene clusters, with no encoded products detected. Deletion of kst cluster led to abolishment of KST an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 57 publications
0
18
0
Order By: Relevance
“…Work will continue to mine these clusters, particularly those with low sequence similarity to known clusters, for novel, antimicrobial compounds. Recently, Zhou et al (2019) [32] forced the production of a different secondary metabolite in Micromonospora sp. TP-A0468 by deletion of the kosinostatin-producing cluster.…”
Section: Discussionmentioning
confidence: 99%
“…Work will continue to mine these clusters, particularly those with low sequence similarity to known clusters, for novel, antimicrobial compounds. Recently, Zhou et al (2019) [32] forced the production of a different secondary metabolite in Micromonospora sp. TP-A0468 by deletion of the kosinostatin-producing cluster.…”
Section: Discussionmentioning
confidence: 99%
“…TP-A0468. [12] These compounds are structurally identical to the known rifamycins except for the absence of the methyl substitute on C16. Homologous genes of orf11 and orf17 are missing in the biosynthetic gene cluster of 16-demethylrifamycins, while the 34a-hydroxylated intermediate 2 is produced.…”
Section: Resultsmentioning
confidence: 86%
“…Given the fact that rifamycin W is accumulated in orf13-missing strains (S. arenicola CNS-205 and Micromonospora sp. TP-A0468) [4,12] but not in orf13-harboring strains (A. mediterranei and A. tolypomycina), [5,17] it could be deduced that orf13 is a reduplicate copy evolved from orf5 to promote the biosynthetic rate of rifamycins. Our work therefore clarifies the function of rif-orf13 in the biosynthesis of rifamycin and explains the contradictory results of previous studies.…”
Section: Discussionmentioning
confidence: 94%
“…strain TP-A0468. [17] Early research on the structure-activity relationship of rifamycin [18] revealed that the oxygen atoms at C-1, C-8, C-23, and C-25 were essential for antibacterial activity. Moreover, the ether bond from oxidative cleavage of C-12 29 μM, respectively.…”
Section: Marine-based Polyketides With Diverse Bioactivitiesmentioning
confidence: 99%
“…The results showed that compound 7 possessed the similar antibacterial activity to rifamycin S, however, compounds 4 -6 were almost inactive under the test conditions. [17] The ether bond from oxidative cleavage of the C-12 (29) double bond was essential for antibacterial activity. The antibacterial activity between 16-demethylrifamycin 7 and rifamycin S showed that the absence of C-16 methyl group does not significantly affect the bioactivity of 16-demethylrifamycins.…”
Section: Marine-based Polyketides With Diverse Bioactivitiesmentioning
confidence: 99%